Lymphangiectatic Kaposi's sarcoma in a patient with AIDS Sarcoma de Kaposi linfangiectásico em paciente com Aids - Mônica Santos; Virginia Vilasboas; Luciana Mendes; Carolina Talhari; Sinésio Talhari (Anais Brasileiros de Dermatologia, 2013)
Kaposi's sarcoma is a malignant disease that originates in the lymphatic endothelium. It has a broad spectrum of clinical manifestations. Its four distinct clinical forms are: classic, endemic, iatrogenic and epidemic Kaposi's sarcoma. In non-HIV-associated Kaposi's sarcoma, the disease is typically limited to the lower extremities, but in immunodeficient patients, it is a multifocal systemic disease. The clinical course of the disease differs among patients, ranging from a single or a few indolent lesions to an aggressive diffuse disease. Advanced Kaposi's sarcoma lesions, typically those on the lower extremities, are often associated with lymphedema. In this paper, we report a case of a patient with a rare form of AIDS-associated Kaposi sarcoma called lymphangiectatic Kaposis's sarcoma. O sarcoma de Kaposi é uma neoplasia originária do endotélio linfatico, que apresenta um amplo espectro de manifestações, com quatro formas clínicas: sarcoma de Kaposi clássico, endêmico, iatrogêncio e epidêmico ou associado ao HIV. Em pacientes imunocompetentes, a doença é tipicamente limitada às extremidades. Porém em pacientes imunideprimidos, o sarcoma de Kaposi é uma doença sistêmica multifocal. Apresenta cursos clínicos diferentes, desde simples lesões cutâneas isoladas até lesões agressivas e difusas, com ou sem envolvimento sistêmico. Lesões avançadas de sarcoma de Kaposi, principalmente as localizadas nas extremidades, podem apresentar linfedema. Neste trabalho, reportamos caso de paciente com forma rara de Sarcoma de Kaposi associado a Aids, chamada de sarcoma de Kaposi linfangiectásico.